Brief on Proceeding of International Conference on Transforming Food Systems through Climate-Smart Agriculture - Belay, Berhanu; Mulatu, Ayalneh (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Accelerating the impact of CGIAR Climate Research in Africa (AICCRA-ILRI) signed a memorandum of understanding (MoU) with 27 public Universities in Ethiopia including Haramaya University to advance research and outreach in the field of climate sciences. Haramaya University and AICCRA – ILRI signed MoU on December, 2021 that will serve from 2011-2023 (Fig 1). As stipulated in MoU, AICCRA-ILRI is fully engaged with Haramaya University in revamping the existing curriculum with contemporary climate products, running short courses in climate risk management in Agriculture (CRMA), thesis examination, advance climate smart small ruminant and organizing international workshop to disseminate climate related research outputs and products.